Coterminous Uppercut: An Analysis of Boxing Metaphors in Selected Ghanaian Political Cartoons - George Boakye-Yiadom (Journal of Language and Literature, 2025)
This study examines the use of boxing metaphors by Ghanaian political cartoonists to communicate socio-political issues, with a particular focus on the depiction of election outcomes and the portrayal of heated arguments or legal disputes.  In order to gain a representative sample, ten political cartoons related to boxing scenes were downloaded from Tilapia of 3 News and Akosua of the Daily Guide. In terms of the theoretical framework that informs this study, Lakoff and Johnson's conceptual metaphor theory (CMT) and Fauconnier and Turner's conceptual blending/integration theory (CBT) are employed in conjunction with Šorm and Steen's VISMIP for the purposes of analysis. The application of CMT to the data led to the identification of conceptual metaphors such as "BOXING IS ELECTION", “WINNING A BOXING MATCH IS WINNING AN ELECTION”, LOSING A BOXING MATCH IS LOSING AN ELECTION and "POLITICAL PARTIES ARE SPORTS TEAMS," etc. The analysis demonstrates that cartoonists employ boxing metaphors to portray electoral outcomes, reflecting the combative and high-stakes nature of Ghanaian elections.  Once more, cartoonists persistently depict the victorious candidates in elections as triumphant boxers. Moreover, the utilization of boxing scenarios in political cartoons by cartoonists facilitates the comprehension of the message, as people are both familiar with and passionate about boxing, thereby rendering the intended meaning more readily understandable. In conclusion, the universality of boxing lends a global dimension to the message, facilitating comprehension of the cartoonist's message by a global audience.